General synthesis of covalent organic frameworks under ambient condition within minutes via microplasma electrochemistry approach - Qi Qing; Junhan Luo; Shuang Liu; Jingyu Wang; Zhe Wang; Xiao-Gen Xiong; Jing Chen; Yuexiang Lu (Nature Communications)
Abstract Covalent organic frameworks (COFs) are typically synthesized using solvothermal conditions with high temperature and long reaction time (≥120 °C, >72 h). Herein, we report a general and rapid microplasma electrochemistry strategy to synthesize COFs under ambient conditions. A series of flexible imine-bond COFs with high-crystallinity were prepared in minutes via this method, which showed 1000-fold higher space-time yield than solvothermal method. This approach also achieved the preparation of COFs with diverse linkages including rigid imine, hydrazone, β-ketoenamies and azine linkages. Moreover, four types of imine-based COFs were successfully synthesized in aqueous acetic acid, which avoided the use of harmful organic solvents, indicating that microplasma method is green and versatile for COF synthesis. The obtained COFs showed higher surface area and exhibited superior performance in volatile iodine uptake compared to those COFs prepared by solvothermal method. After screening more than ten types of COFs, the iodine adsorption capacity could be promoted from 2.81 to 6.52 g g−1. The efficiency, versatility, and simplicity of the microplasma method render it as a promising approach for the swift screening of COFs across a wide range of applications.